Experiments on micrometer and nanosizes of shale and lateritic rock as colorants on canvas / Hushinaidi Abdul Hamid - Abdul Hamid, Hushinaidi (Institute of Graduate Studies, UiTM, 2012)
Malaysian lands are very rich in natural resources especially Shale and Lateritic rocks. The transformations of coloured rocks to colorants for artwork can give a huge impact for the government, industries and consumer. This research project aimed to process and produce natural colorants from shale and lateritic rocks into two sizes which are in micrometer and nano size range. X-Ray Fluorescent (XRF) was carried out to identify element content in each rock whilst Field Emission Scanning Electron Microscopy (FESEM) was performed in order to determine the sizes of the rocks after grinding accurately.